Development Of Teaching Modules Oriented Towards Realistic Mathematics Education With Luwu Cultural Context, Integrated With The Pancasila Student Profile and High Order Thinking Skills. - Baharuddin, Muhammad Rusli; Taufiq, Taufiq; Fitriani, Fitriani; Patmaniar, Patmaniar; Wafda, Andi (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2025)
The development of students' potential in learning must be carried out holistically and comprehensively. However, many teachers still struggle to design teaching modules that align with the Merdeka Curriculum and learning needs. This study aims to develop a Merdeka Curriculum Teaching Module oriented towards Realistic Mathematics Education (RME) with a Luwu Cultural context, integrated with the Pancasila Student Profile. The assessment results indicate that this teaching module is effective in improving students' Higher-Order Thinking Skills (HOTS). The validity score shows an average of 77.78%, classified as valid, reflecting the quality of the module in terms of material relevance, completeness of information, and clarity of presentation. The practicality assessment of the teaching module also scored an average of 88%, indicating that the module is highly practical and easy to implement in daily learning. The practicality aspects include ease of use, learning effectiveness, and time efficiency. In the evaluation of students' HOTS abilities, the NSI category indicates that 6% of students still require special intervention, while the Mastery category shows that around 5% of students have excellent HOTS. Most students fall into the Basic and Proficient categories, indicating that the module is effective in developing students' basic and intermediate skills. The practical implications of this research are that the developed teaching module can assist teachers in effectively implementing learning based on the Merdeka Curriculum, integrating local cultural values and the principles of the Pancasila Student Profile. Moreover, the module is considered practical for daily use in the classroom, making a tangible contribution to improving the quality of education in schools.